Carbono no solo e correlações com a dinâmica da paisagem: contribuição para o planejamento e gestão da bacia hidrográfica do rio Umbelúzi – Moçambique - Jalane, Orlando Inácio (2020)
The Umbelúzi river basin is located in the south of Mozambique, in the Maputo province, probably the most intensive soil use place, highly pressured by atrophic actions. They are variety of landscape units with different economic activities, which not always adjusted to the environment when consider the basin, as an environmental basis for analysis, the research aimed to present a proposal for an integrated analysis of environmental, economic and social factors in the landscape dynamics. To achieve the propose, the research was developed by the modelling of soils carbon stocks in the range of 0 to 30 cm, to contribute in the environmental planning for the catchment area. Using integrated landscape studies and the geo-technology applied to the planning and management of natural factors that influence good human practices. In order to contribute with technical scientific instruments to aid decision-making for the improvement of environmental quality in the Umbelúzi River catchment land. The research follows six steps to achieve the proposed objective and it was carried out on a base scale of 1: 250,000, which satisfies the representation of basins with larger area than 1000 square meter. The results demonstrate that there is an influence between the basin's landscapes and the dynamics of carbon in the soil, and with the increase of atrophic activities in the landscape, the disposition of carbon in the soil and its function as an environmental and soil health regulator has changed. Land use is related to economic systems and causes changes in natural systems, which change and create consequences such as erosion, floods, droughts, loss of homes, deaths, etc., interfering with social factors, such as food insecurity and extreme poverty.